Comparative study of gamma-ray shielding features and some properties of different heavy metal oxide-based tellurite-rich glass systems. (May 2020) - Lakshminarayana, G.; Kumar, Ashok; Lira, A.; Dahshan, A.; Hegazy, H.H.; Kityk, I.V.; Lee, Dong-Eun; Yoon, Jonghun; Park, Taejoon
Abstract: Tellurite-rich glasses containing Sm 3+, Dy 3+, and Er 3+ ions with nominal chemical composition of 69 TeO2 ‒10 Bi2 O3 ‒10 BaO‒10 ZnO‒1.0 Sm2 O3 /1.0 Dy2 O3 /1.0 Er2 O3 (mol%) were fabricated. The gamma radiation attenuation features of the synthesized glasses were compared with two other tellurite glass systems with the chemical composition of 68 TeO2 ‒(22-x) Bi2 O3 ‒10 ZnO‒ (x) PbO (x = 10, 12, 14, 16 and 18 mol%), and 75 TeO2 ‒20 B2 O3 ‒5 Mx Oy (mol%) (Mx Oy  = WO3, Nb2 O5, PbO, Nd2 O3, Y2 O3 ). The mass attenuation coefficients (μ/ρ) (MAC) were computed from 0.015 MeV to 15 MeV photon energies using the XCOM program. Using the obtained μ/ρ values, effective atomic number (Zeff ), electron density (Ne ), half-value layer (HVL) and mean free path (MFP) were determined at different photon energies. The results clearly reveal that the MAC depends upon the heavy metals present in the studied glasses, and such addition increases the shielding capabilities of the samples against the gamma radiation. The Zeff and Ne confirmed the shielding effects with a variation in heavy metals content. The HVL and MFP values indicate the potential application in radiation insulation with less probability of interactions with gamma photons in the investigated tellurite glasses. It is found that the HVL or MFP values of the A ‒ C glasses lies in between the HVL or MFP values of the S1 – S5 and the T1 ‒ T5 glasses, respectively. Thus, the synthesized glasses are better shielding materials than the T1 – T5 glasses and possess slightly less gamma-ray shielding capacity than that of S1–S5 glasses. Highlights: Singly Sm 3+, Dy 3+, and Er 3+ -doped TeO2 –Bi2 O3 –BaO– ZnO glasses were synthesized. Raman spectral results confirmed mainly the TeO4 and TeO3+1 /TeO3 structural units. Judd-Ofelt intensity parameters (Ω2, Ω4, and Ω6 ) and radiative features are evaluated. XCOM software program is used to calculate 'μ/ρ' values at different photon energies. Various radiation shielding features are compared with other tellurite glass systems.